2003
DOI: 10.2355/isijinternational.43.1630
|View full text |Cite
|
Sign up to set email alerts
|

Nucleation of Proeutectoid Ferrite on Complex Precipitates in Austenite

Abstract: Effect of various intragranular inclusions or precipitates (MnS, VC and V(C,N)) on the microstructure and kinetics of intragranular ferrite transformation at the temperatures between 973 and 823 K was studied using various Fe-2Mn-(0.13, 0.2)C(mass%) alloys with the small addition of sulfur, vanadium, and nitrogen. In Fe-2Mn-0.13C-50ppmS and Fe-2Mn-0.2C-470ppmS alloys, MnS particles, mostly incoherent in austenite, do not act as effective nucleation sites of ferrite. V addition slightly improves the potency of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
73
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(82 citation statements)
references
References 24 publications
7
73
0
2
Order By: Relevance
“…These pure MnS inclusions are not active nucleants for acicular ferrite, because they are incoherent in austenite. 53) Moreover, they also have the least difference in thermal expansion coefficient from austenite, as shown in Fig. 10.…”
Section: Sulfidesmentioning
confidence: 90%
See 3 more Smart Citations
“…These pure MnS inclusions are not active nucleants for acicular ferrite, because they are incoherent in austenite. 53) Moreover, they also have the least difference in thermal expansion coefficient from austenite, as shown in Fig. 10.…”
Section: Sulfidesmentioning
confidence: 90%
“…Miyamoto et al 87) and Furuhura et al 53,54) observed that the addition of about 0.3 % V and 0.01 % N to a low-carbon steel makes it more effective in nucleating AF. This was due to the formation of MnS-V(C, N) complex precipitates.…”
Section: Complex Oxy-sulfides and Multi-phase Inclusionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, He and Edmonds [24] speculated that the formation of Fe-V clusters could act as nucleation sites for acicular ferrite in addition to inclusions. Furthermore, Furahara et al [25] showed that addition of V and N to C-Mn steel containing MnS inclusions led to the formation of acicular ferrite. Above discussion probably suggests that increase in hardenability elements in weld deposits with nano-size TiO 2 allows for greater under cooling as well as favorable inclusion characteristics for greater possibility of acicular ferrite formation.…”
Section: Microstructure and Mechanical Propertiesmentioning
confidence: 99%